Upaya Pencegahan Perilaku Bullying Anak Usia SD Melalui Kegiatan Sosialisasi Di SD Negeri 1 Jamblang - Ambarwati Imtiyas; Andine Rizki Kurnia; Livia Livia; Tiyara Maharani; Sati Sati; Dian Setiawati (Mathematics Education Study Program, 2025)
Bullying behavior in elementary school environments often occurs due to students' lack of understanding of its negative impacts. The Student Service Program at SDN 1 Jamblang aims to prevent bullying, intolerance, and sexual violence through three phases: planning, implementation, and evaluation.The planning phase includes the creation of materials, data collection, and activity preparation. The implementation phase involves delivering materials, interactive discussions, and creating